Complete mitogenomes of two major dengue vectors Aedes aegypti and Aedes albopictus from Bangladesh: Insights from comparative genomics with global mitogenome diversity and phylogenetics - Md. Aminul Islam; Shefali Begum; Morjina Solaiman; Fatema-Tuz- Zohora; Sujan Kumar Datta; Khandaker Asif Ahmed; Md. Sagir Ahmed (PLoS ONE, 2025)
Aedes aegypti and Aedes albopictus are the most competent vectors of multiple human arboviral diseases, posing a global public health concern, particularly in Bangladesh. While there are numerous genomic resources available worldwide, the genomic resources from Southeast Asian countries are scarce. Current study reported the first characterization of the complete mitochondrial (mt) genomes of Ae. aegypti and Ae. albopictus from Bangladesh. The circular mitogenomes are 16,662 bp and 16,585 bp in size, with AT contents of 79.02% and 78.81%, respectively. Both mitogenomes contain all 37 functional subunits, including 13 protein-coding genes (PCGs), two ribosomal RNA genes, 22 transfer RNA genes (tRNAs), and a control region. We also reported the unique codon usage and Relative synonymous codon usage patterns, which are congruent with other members of the Culicine family. Our intraspecific analysis of 15 mitochondrial genes revealed higher genetic distance, but lower SNP density in Ae. aegypti, compared to Ae. albopictus, indicating Ae. aegypti might have a longer evolutionary history, while Ae. albopictus might have experienced recent population expansion with steady divergence. Similarity metrics and phylogeny of 13 PCGs from 37 taxa indicated both species of Aedes formed specific clusters, where Bangladeshi Aedes spp. showed close relationships with North American, Oceania and European populations. Our comprehensive tree incorporating Aedes, Ochleroratus and Culex spp. revealed distinct clades, aligning with previous studies. Current study provides a foundation for future research on Aedes spp. of Bangladesh, leveraging it to other Southeast Asian countries, aiding vector identification, control, and disease mitigation.